How Does Flipped Learning Work? A Case Study in Signals and Systems Teaching - Ana Carolina Useche; Jairo A. Hurtado (Education Sciences, 2025)
Student-centered teaching approaches emphasize student responsibility and learning. Flipped learning is a student-centered approach to promoting student learning. In this paper, we describe a flipped learning strategy that involves fostering collaborative, problem-based, and project-based learning in engineering courses. In addition, we delineate the role of student assessment and teacher–student interactions in the flipped learning teaching strategy. In this study, we compare academic achievement and student perceptions of instruction in a lecture-based and a flipped classroom. The results show that the students in a flipped classroom had higher grades than those in a lecture-based classroom. In addition, students in the flipped classroom assessed the learning materials, activities, and evaluations more positively than the students in the lecture-based classroom did. Students in the flipped classroom were also found to be more likely than those in the other class to perceive that they could apply the knowledge and skills they developed in the course. They also had higher motivation to learn than the students in the lecture-based class and perceived that the instructor generated a positive climate that fostered student participation.